Artificial microRNA-mediated resistance against Oman strain of tomato yellow leaf curl virus - Al-Roshdi, Maha R.; Ammara, Ume; Khan, Jamal; Al-Sadi, Abdullah M.; Shahid, Muhammad Shafiq (Frontiers in Plant Science, 2023)
Tomato yellow leaf curl virus (TYLCV) is a global spreading begomovirus exerting a major restraint to the world tomato production. In this transgenic approach, an RNA interference (RNAi) based construct consisting of sequences of an artificial microRNA (amiRNA), a group of small RNA molecules necessary for plant cell development, signal transduction and stimulus to biotic and a biotic disease was engineered targeting AC1/Rep gene of Oman strain of TYLCV-OM. The Rep-amiRNA constructs presented an effective approach in regulating the expression of Rep gene against TYLCV as a silencing target to create transgenic Solanum lycopersicum L. plant tolerance against TYLCV infection. Molecular diagnosis by PCR followed by a southern hybridization analysis were done to confirm the effectiveness of agrobacterium-mediated transformation in T0/T1 transformed plants. Substantial decrease in virus replication was observed when T1 transgenic tomato plants were challenged with TYLCV-OM infectious construct. Although natural resistance option against TYLCV infection are not accessible, the outcomes of this study advised that transformed plants expressing amiRNA could be an essential approach for engineering tolerant plants against TYLCV infection and conceivably for the inhibition of viral disease against different strains of whitefly transmitted begomoviruses in Oman.